Effect of land use change on chemical properties of a vertisol. - Yáñez Díaz, María Inés; Cantú Silva, Israel; González Rodríguez, Humberto (REVISTA TERRA LATINOAMERICANA, 2018)
Chemical properties are indicative of soil quality, and nutrient reserves can be modif ied by anthropogenic activities. To evaluate the effect on the chemical properties of vertisol-type soil, nutrients were analyzed under four land use systems in northeastern Nuevo Leon, Mexico: Tamaulipan thornscrub, grassland, agricultural crop and eucalyptus plantation. Four compound soil samples were collected per site at two depths (0-5 cm and 5-30 cm), and the variables pH, electrical conductivity (EC), cation exchange capacity (CEC), macronutrients (K, Ca, Mg and Na) and micronutrients (Cu, Mn, Fe and Zn) were determined. According to the results obtained, differences (P ≤ 0.05) were found between system use for pH, Mg (cmol(+) kg‑1), Fe (mg L‑1) and Cu (mg L-1) in the two depths. CE (dS m-1), Zn (mg L-1) and CEC (cmol(+) kg‑1) showed differences in depth 0-5 cm, while Ca, (cmol(+) kg‑1), Na (cmol(+) kg-1) and Mn (mg L‑1) for depth 5-30 cm. Nutrients P (mg kg‑1) and K (cmol(+) kg-1) were not different between systems at the two depths. A Spearman correlation analysis was made between variables; pH was the variable that was associated with most of the nutrients due to competition among cations and the effect of micronutrient availability. In the agricultural systems and eucalyptus plantation, there was decrease in K, Fe, Mn, Zn and CEC, whereas in the grasslands contents of P and K increased in contrast with thornscrub that represents the natural vegetation.